2016
DOI: 10.1111/acel.12521
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β‐induced astrogliosis is mediated by β1‐integrin via NADPH oxidase 2 in Alzheimer's disease

Abstract: SummaryAstrogliosis is a hallmark of Alzheimer 0 s disease (AD) and may constitute a primary pathogenic component of that disorder. Elucidation of signaling cascades inducing astrogliosis should help characterizing the function of astrocytes and identifying novel molecular targets to modulate AD progression. Here, we describe a novel mechanism by which soluble amyloid-b modulates b1-integrin activity and triggers NADPH oxidase (NOX)-dependent astrogliosis in vitro and in vivo. Amyloid-b oligomers activate a PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 46 publications
4
57
0
Order By: Relevance
“…A large number of possible Aβ receptors have been suggested (Jarosz-Griffiths et al, 2016). Interaction between integrins, a large family of extracellular matrix receptors, and Aβ peptides promote neurotoxicity and inhibition of LTP (Wang et al, 2008), mitochondrial and synaptic dysfunction (Woo et al, 2015), gliosis (Wyssenbach et al, 2016) and oligodendrocyte differentiation Quintela-López et al, 2019). In the developing and adult brain, many integrins are present at high levels at synapses (for review, Park and Goda, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of possible Aβ receptors have been suggested (Jarosz-Griffiths et al, 2016). Interaction between integrins, a large family of extracellular matrix receptors, and Aβ peptides promote neurotoxicity and inhibition of LTP (Wang et al, 2008), mitochondrial and synaptic dysfunction (Woo et al, 2015), gliosis (Wyssenbach et al, 2016) and oligodendrocyte differentiation Quintela-López et al, 2019). In the developing and adult brain, many integrins are present at high levels at synapses (for review, Park and Goda, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Selective loss of this receptor in excitatory neurons leads to reductions in the size and complexity of hippocampal dendritic arbors, hippocampal synapse loss and impaired hippocampusdependent learning (Warren et al, 2012). Additionally, integrin β1 mRNA and protein levels are upregulated by Aβ oligomers in astrocytes and oligodendrocytes suggesting that Aβ peptides might change the dynamic nature of integrin expression and function throughout AD (Wyssenbach et al, 2016;Quintela-López et al, 2019). Notably, we observed that spine density and specifically the fraction of stubby spines returned to control levels when integrin β1 was reduced with blocking antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(23,35,36,53,54). The close relationship between the levels of Aβ and NOX2 activity has also been well documented in multiple studies (22,38,(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 76%
“…In the meantime, SCI triggers astrocytes to become reactive and initiate astrogliosis [ 31 , 32 ]. Reactive astrogliosis is characterized by the proliferation and hypertrophy of astrocytes, which eventually leads to scar formation via the effects of neurotrophic factors such as BDNF [ 33 ], or activation of signaling pathways such as STAT3, transforming growth factors-β (TGF-β/Smad) and PI3K [ 12 , 32 , 34 37 ]. Upon injury, astrocytes undergo phenotypic and morphologic changes.…”
Section: Discussionmentioning
confidence: 99%